2020
DOI: 10.1093/emph/eoaa022
|View full text |Cite
|
Sign up to set email alerts
|

Immune function during pregnancy varies between ecologically distinct populations

Abstract: Abstract Background and objectives Among placental mammals, females undergo immunological shifts during pregnancy to accommodate the fetus (i.e. fetal tolerance). Fetal tolerance has primarily been characterized within post-industrial populations experiencing evolutionarily novel conditions (e.g. reduced pathogen exposure), which may shape maternal response to fetal antigens. This study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…We included body mass index (BMI) and age as covariates in all models, and included a pregnancy covariate for women (0/1) [ 44 ]. The small number of pregnant women ( n = 6) precluded a trimester-level analysis [ 45 ]. We included only STHs with >10% prevalence across the sample set.…”
Section: Methodsmentioning
confidence: 99%
“…We included body mass index (BMI) and age as covariates in all models, and included a pregnancy covariate for women (0/1) [ 44 ]. The small number of pregnant women ( n = 6) precluded a trimester-level analysis [ 45 ]. We included only STHs with >10% prevalence across the sample set.…”
Section: Methodsmentioning
confidence: 99%
“…We included body mass index (BMI) and age as covariates in all models, and, in the female specific models, included a covariate for pregnancy (0/1) [47]. While previous research in the Tsimane has shown differences in immune function by trimester, the small number of pregnant women (n=6) in this study precluded a trimester-level analysis [48]. We included in our models only STHs with a prevalence of over 10% across our sample set.…”
Section: Statistical Analysis 261 Effect On Individual Cytokine Responsesmentioning
confidence: 99%
“…Because of the lack of standard health surveillance in the region, we are unable to know for certain if study participants had previously been exposed to H1N1, which would shape the interpretation of our results. We know that immunological changes during pregnancy vary by trimester [48], but our low sample size of pregnant women precluded a trimester-level analysis. We also did not include children in our analyses and thus cannot assess the role of early life exposure in this relationship.…”
Section: Limitationsmentioning
confidence: 99%
“…Pregnancy is a state characterized by profound hematological changes, and regulated inflammation which is consistently marked by a rise in the total number of circulating leukocytes, primarily due to the increase of neutrophils and monocytes. These phagocytic cells can also induce inflammatory activation and strengthen resistance to extracellular infections, but are also associated with the etiology of autoimmune diseases [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunity in pregnancy is physiologically compromised and may affect the CD 4 + cell count, as lower CD 4 + cell count has been reported in pregnant compared with non-pregnant females [ 15 ]. On the other hand, total lymphocyte counts are consistently reduced during pregnancy, primarily due to fewer circulating cytotoxic lymphocytes capable of directly recognizing and targeting fetal antigens [ 14 ]. On the contrary CD4 T cells, the proliferation of regulatory lymphocytes is increased [ 16 ].…”
Section: Introductionmentioning
confidence: 99%